Why do bank-dependent firms bear interest-rate risk? - Kirti, Divya (Journal of Financial Intermediation, 2020)
I document that floating-rate loans from banks, particularly important for bank-dependent firms, drive most variation in firms’ exposure to interest rates. I argue that banks prefer to supply floating-rate loans, due to their finite ability to transform short-duration deposit liabilities into long duration assets. Three key findings support this argument: banks with more floating-rate liabilities make more floating-rate loans, hold more floating-rate securities, and quote lower prices for floating-rate loans. Intermediary funding structures therefore help determine what types of contracts non-financial firms use. Banks transmit rising policy rates to firms by contractually raising interest rates on existing loans, not just by reducing the supply of new loans.